Aktivitas Antimikroba Bronok (Acaudiana molpadiodes) Dari Perairan Moro Kepulauan Riau - SUHAERA, SUHAERA; Rachmayanti, Aprilya Sri (Medihealth: Jurnal Ilmu Kesehatan dan Sains, 2022)
Bronok (Acaudina molpadioides) is one of the marine biota which based on empirical evidence from the community is believed to have health benefits. However, it has not become a commodity that has high economic value. The aim of the study was to determine whether the bronchus extract could inhibit the growth ofStaphylococcus epidermidis bacteria, and the fungus Candida albicans. Bronchi extract was prepared by maceration method with methanol, ethyl acetate, and N-hexane as solvents. The results of the extraction were carried out by phytochemical screening tests, then continued with antimicrobial activity tests using the paper disc diffusion method with concentrations of 25%, 50%, 75%, and using positive controls ciprofloxacin (bacteria), ketoconazole (fungi) and negative controls DMSO. The results showed that the extract of methanol, ethyl acetate, n-hexane bronchi did not inhibit the growth of Staphylococcus epidermidis bacteria.Meanwhile, Candida albicans has inhibitory power at 50% concentration of 7.85 mm and 75% concentration of 8.95 mm